2020
DOI: 10.31044/0543-5846-2021-60-59-62
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of deformation bands in a low-carbon steel – stainless steel bimetal

Abstract: The regularities of non-uniform plastic deformation evolving on the Lüders bands are studied in a low carbon steel-austenite stainless steel bimetal via a digital image speckle method. The local strain distributions in the bimetal low-carbon steel base layer at the yield point stage are presented by the two strain localization bands that are similar to the Lüders bands. Analogous distributions arise at the yield point from the bimetal austenite stainless steel clad layer in the form of two strain localization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…When higher thermal conductivity metal (copper) is employed as interlayer, thermal energy transmitted into the participant metals is higher and consequently formation of intermetallic compounds is witnessed at the interface (Figure 4.a). Samardzic et al [21] while joining zirconiumsteel with a titanium interlayer reported molten layer in the first interface and reported the difference in thermal properties inducing this phenomenon. The higher density of copper also enhances the kinetic energy utilization in creating plastic deformation and consequently more work done.…”
Section: Microstructure Interprementioning
confidence: 99%
“…When higher thermal conductivity metal (copper) is employed as interlayer, thermal energy transmitted into the participant metals is higher and consequently formation of intermetallic compounds is witnessed at the interface (Figure 4.a). Samardzic et al [21] while joining zirconiumsteel with a titanium interlayer reported molten layer in the first interface and reported the difference in thermal properties inducing this phenomenon. The higher density of copper also enhances the kinetic energy utilization in creating plastic deformation and consequently more work done.…”
Section: Microstructure Interprementioning
confidence: 99%
“…Gonzaga [ 13 ] demonstrated that ductile iron with a matrix structure 30% of ferrite and 70% of pearlite has the highest fracture toughness, yield strength, and hardness. Bockus and Zaldarys [ 14 ] studied the effect of section thickness on graphite parameters of ductile iron and reported that the diameter of the spheroids increases with an increase in section thickness. Shinde et al.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical framework by various previous researchers has considered a constant voidage model for the packed bed [1720], a two-fluid model for the gas and fines flow [21,22], an isostress based model for determining the raceway shape and size [23,24], and a correlation-based static holdup [24]. Similar mathematical framework has been employed by several researchers to replicate the holdup [9,22,2530] and pressure loss characteristics [31,32] in a blast furnace.…”
Section: Introductionmentioning
confidence: 99%